Restoration of degraded sites with suitable tree species in the Mid-hills of Nepal - Jha, R K; Baral, S K; Aryal, R; Thapa, H B (Banko Janakari, 2016)
Land degradation is a major challenge in Nepal. A lot of degraded land is available within the Community Forests in the Mid-hills which are being aimed to be utilized for ecological restoration as well as supporting livelihoods of the local people. In this context, the study was conducted in the Chautaradanda Community Forest (27°44’05’’ N and 85o04’60’’ E) of Thakre Village Development Committee of Dhading District in the lower Mid-hills of Central Nepal to test the survival capacity and growth performance of different tree species (native, naturalized as well as exotic) that can be used for the rehabilitation of degraded sites. Firstly, Stylo (Stylosanthes spp.), a leguminous grass, was introduced on a degraded site for enriching nutrients in June 2008. Secondly, six different native, naturalized as well as exotic tree species (Sapindus mukorossi, Prunus cerasoides, Choerospondias axillaris, Melia azedarach, Pinus patula and Robinia pseudoacacia) were planted in a randomized complete block design with 4 blocks (6 species × 4 blocks) in July 2008. The results showed that the growth and survival rate of exotic species, P. patula was outstanding; however, the performance of its native and naturalised counterparts P. cerasoides, C. axillaris and M. azedarach was found to be satisfactory. R. pseudoacacia was not found to be a suitable species for rehabilitating degraded sites in the lower Mid-hills of Nepal. Therefore, it would be wise to select the native or naturalized species for the rehabilitation of degraded sites in the Mid-hills, as sometimes the introduction of exotic species may have pessimistic ecological consequences; however, P. patula can be used as it has not shown any invasive nature since its introduction (around 1980s) in the Mid-hills of Nepal. Hence, the study shows the possibility of introducing the tree species such as P. cerasoides, M. azedarach and C. axillaris for ecological restoration of degraded sites in the Community Forests in the Mid-hills of Nepal. Banko Janakari, Vol. 23, No. 2